Deletion of Akt1 Promotes Kidney Fibrosis in a Murine Model of Unilateral Ureteral Obstruction. (24th November 2020) - Kim, Il Young; Lee, Min Young; Park, Mi Wha; Seong, Eun Young; Lee, Dong Won; Lee, Soo Bong; Bae, Sun Sik; Kim, Sang Soo; Song, Sang Heon
Abstract : We investigated the role of Akt1, one of the three isoforms of Akt, in renal fibrosis using the murine model of unilateral ureteral obstruction (UUO). We subjected wild type and Akt1 −/− mice to UUO. The Akt1 gene was silenced in vitro using short hairpin RNA delivered via a lentiviral vector in human proximal tubular cells (HK2 cells) and kidney fibroblasts (NRK-49F cells). The obstructive kidneys of Akt1 −/− mice showed more severe tubulointerstitial fibrosis than those of wild type mice. The expression of fibronectin and type I collagen was significantly increased in obstructed kidneys of Akt1 −/− mice compared to those of wild type mice. The important finding was that the expression of transforming growth factor β 1 (TGF β 1) was significantly increased in the Akt1 −/− mice compared to the wild type mice. The knockdown of Akt1 enhanced the expression of TGF β 1 in HK2 cells. Interestingly, the upregulation of TGF β 1 due to genetic knockdown of Akt1 was associated with activation of signal transducer and activator of transcript 3 (STAT3) independently of the Smad pathway in NRK-49F and HK2 cells. Immunohistochemical staining also showed that expression of phosphorylated STAT3 was more increased in Akt1 −/− mice than in wild type mice after UUO. Additionally, the deletion of Akt1 led to apoptosis of the renal tubular cells in both in vivo and in vitro studies. Conclusively, these results suggest that the deletion of Akt1 may contribute to renal fibrosis via induction of the TGF β 1/STAT3 pathway in a murine model of UUO.